ARHGAP21 Protein, a New Partner of α-Tubulin Involved in Cell-Cell Adhesion Formation and Essential for Epithelial-Mesenchymal Transition - Barcellos, Karin S. A. (American Society for Biochemistry and Molecular Biology, 2013)
Cell-cell adhesions and the cytoskeletons play important and coordinated roles in cell biology, including cell differentiation, development, and migration. Adhesion and cytoskeletal dynamics are regulated by Rho-GTPases. ARHGAP21 is a negative regulator of Rho-GTPases, particularly Cdc42. Here we assess the function of ARHGAP21 in cell-cell adhesion, cell migration, and scattering. We find that ARHGAP21 is localized in the nucleus, cytoplasm, or perinuclear region but is transiently redistributed to cell-cell junctions 4 h after initiation of cell-cell adhesion. ARHGAP21 interacts with Cdc42, and decreased Cdc42 activity coincides with the appearance of ARHGAP21 at the cell-cell junctions. Cells lacking ARHGAP21 expression show weaker cell-cell adhesions, increased cell migration, and a diminished ability to undergo hepatocyte growth factor-induced epithelial-mesenchymal transition (EMT). In addition, ARHGAP21 interacts with α-tubulin, and it is essential for α-tubulin acetylation in EMT. Our findings indicate that ARHGAP21 is a Rho-GAP involved in cell-cell junction remodeling and that ARHGAP21 affects migration and EMT through α-tubulin interaction and acetylation.